Adjustment and Other Factors Related to High School Aged Students Identified as Hearing Impaired - Charlene Milano; Tara Upshire; Sarah Scarazzo; Benjamin P. Schade; Karen H. Larwin (Institute of Advanced Engineering and Science, 2016)
Healthy social, emotional and cognitive development of deaf children depends upon complex interactions between the many individual and environmental factors associated with deafness. Deaf children and adolescents have been reported to possess greater rates of mental health problems than hearing children and adolescents. Dysfunction in one or more systems impacts the other systems in the child’s life. Dysfunction increases the risk for maladjustment and poor mental and emotional health. Deaf youth are at greater risk for disruption in interactions between the child and their environment and therefore are also at greater risk for social and emotional problems. Data from the National Longitudinal Study of Adolescent to Adult was used to gain a better understanding of deaf student’s feelings of acceptance at school, reported positive feelings, academic grades and future plans. Twelve (12) deaf students were included in a total of 456 youth participants from across the county. No significant differences were found between the two groups.